Entre a cordialidade e o branquíssimo: o discurso racista na representação social da pessoa negra no jornal Folha de S. Paulo - Sousa, Aryclennys Silva (2019)
The present study has as main objective to verify how the discourse of racism manifests, articulating the communication, social representation, citizenship and the categorization of the modalities of expression of discrimination, prejudice and racism identified by science. Thus, 42 journalistic articles published in the Folha de S. Paulo newspaper were analyzed during the celebrations of the National Black Consciousness Day, on November 20 and 21, from 2012 until 2017, using as theoretical contribution of the Theory of Social Representations, postulated byMoscovici (1978), and methodological developed by Abric, Central Nucleus Theory (TNC) or structural theory. In general, bibliographic research seeks to identify, in the last instance, the social representation of the black person that circulates and is expressed by one of the largest newspapersin the country. The results indicate that the social and media representation of the black person is mostly concentrated in the status of enslaved Brazilian colony, especially in the figure of a child with a certain basic academic, cultural and intellectual level. The black person has a citizenship that guarantees only political rights. In addition, it composes the social representation, the discursive modality of Prejudice Theories, along with the ideology of whitening the Brazilian black population, so that the forms of expression of racist discourse in Brazil demonstrate the faces of racism, discrimination, prejudice, disaffection, enmity and repudiation of the white against the Brazilian Negro. Thus, the black person has a denied citizenship (DURSTON, 1999), becoming part of the population group with status of sub-citizen of (SOUZA, 2003), remaining, in summary, below citizenship, in a lower category (TUZZO, 2014).